Corrections - Discussion of Metallurgical Testing Procedures in Use at Pima Mining Co - D. C. Shelton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
Eq. 4 and 5 on page 5 of the March 1965 issue of Transactions, and Eq. 12 on page 8 of the same issue should read respectively: